The legacy and heritage of Loke Chow Kit - Junn, Ng 1965-; Ch'ng, Symn (CGB Consultants Sdn Bhd, 2020)
Many people know of the Chow Kit district in central Kuala Lumpur, but not many know of the man it was named after. In The Legacy and Heritage of Loke Chow Kit, the vast history left behind by Loke Chow Kit and his Malaya that we know and love today is fully explored. Beautifully designed and illustrated with more than 300 images, the book covers Loke Chow Kit?s personal life and many businesses, and has a particular focus on the tangible cultural heritage that was associated to him in the past that can still be seen in the present. A beacon and figurehead of the Malayan community, Loke Chow Kit?s contribution is finally acknowledged and immortalised in this book.